Marketing Strategy Analysis in Increasing Participation Numbers in the Social Security Administration for Employment (BPJS Ketenagakerjaan) Tanjung Perak Branch Office Using SWOT Analysis Method - Azizah, Shinta Rizki; Iriani, Iriani (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
This study delves into the societal responsibility of nations for ensuring the well-being of their citizens through the implementation of social welfare systems, notably the social security program managed by the Social Security Organizing Agency (BPJS). The historical evolution of PT Jamsostek (Persero) underscores the development of social security programs in Indonesia, emphasizing the significance of safeguarding workers' economic and social interests. This research focuses on BPJS Ketenagakerjaan Tanjung Perak Branch, aiming to analyze its marketing strategies to augment membership through the SWOT analysis method. Employing a qualitative approach, the study employs interviews, observations, and documentation for data collection. The findings reveal strengths in BPJS Ketenagakerjaan's extensive social security offerings, weaknesses in communicating with and raising awareness among informal workers, opportunities for enhancing worker welfare, and threats posed by declining membership due to competitive forces. Drawing on the SWOT analysis, the study suggests a conglomerate diversification strategy, wherein BPJS Ketenagakerjaan Tanjung Perak can introduce new programs to previously untapped segments, thus bolstering its membership base. The research enriches the understanding of BPJS Ketenagakerjaan's marketing strategies and contributes insights for broadening its membership outreach.